Foreign direct investment and international law : liberalization and economic sovereignty - Aniodoh, Adaeze Agatha (Routledge, 2026)
"This book examines the regulatory framework for foreign direct investments, most notably the bilateral investment treaties which provide several guarantees that minimise the exposure of risks to foreign investors in a host State. Most States have recognised that one of the ways they can improve their economic growth is by providing effective mechanisms for the attraction of foreign investments. In this regard, foreign direct investments have become a key element in the strategic vision for advancing any national economy. The book examines guarantees which have the capacity to impinge on the economic sovereignty of a State raising questions such as: are host States obliged to comply with the rights of foreign investors to free capital repatriation in the face of economic difficulties? What power does a host State have to regulate and impose capital controls that are deleterious to the rights of a foreign investor? This book argues that policies aimed at increasing foreign direct investment need to extend beyond investment liberalisation, to strike a balance between the regulatory rights of a State and the legitimate expectations of foreign investors. Advancing the discussion on the necessity of balancing the needs of foreign investors with those of the host community, and exploring the power asymmetry present in treaty negotiations, this book will be of interest to students, academics, and practitioners with an interest in international investment law"-- Provided by publisher.
Keywords: Investments, Foreign -- Law and legislation.; Investments, Foreign (International law); Capital movements -- Law and legislation.; Commercial treaties.; elektronické knihy; electronic books